Development of Virtual Reality Hydroelectric (VIRRIC) for teaching students about renewable energy - Zakaria, Aminudin; Anggaryani, Mita (Universitas Muhammadiyah Mataram, 2024)
Understanding abstract physics theories, such as energy, can be challenging for students. Teachers also face the difficulty of meeting learning objectives within limited classroom time. The purpose of this research is to develop physics learning media to teach high school students about renewable energy. The learning media is presented as virtual reality, focusing on the energy conversion process in hydroelectric power plants. The goal is for students to apply their understanding of energy conversion concepts in hydroelectric power plants as one type of renewable energy source. The research process follows the ADDIE model, focusing on the analysis, design, and development stages. Data is collected through validation sheets completed by media experts, which provide valuable suggestions for revisions. The data was analyzed using descriptive statistical methods. It is known that at this level of education, the cognitive level required for understanding renewable energy material is C4 according to the revised Bloom's taxonomy. At the design stage, storyboards are used to frame the media development process, comprising a problem orientation scene and an exploration scene. After development, the VIRRIC media was validated based on visual aspects, interest, usefulness, accuracy, legitimacy, and structure. The final media expert validation score for the VIRRIC media is 0.87, categorized as highly valid. The lowest score was in the visual aspect, which was 0.77. This was due to some text information in the media being difficult to read. The text is observable when not using a gyro device, but becomes difficult to read when observed using a gyro device. Based on these results, the VIRRIC media is deemed suitable for testing in learning after making improvements.